A Brief Study of Natural Drug Camptothecin - Seema Manchanda (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
20-(S)-Camptothecin (CPT) is a natural alkaloid extracted from the bark of Camptotheca acuminata (Chinese happy tree). It acts as a DNA topoisomerase 1 poison with an interesting antitumor activity and its use is limited by low stability and unpredictable drug-drug interactions. Since the late 20th century, it has been widely used in cancer therapy and, since extraction yields from plant tissues are very low, various synthetic routes have been developed to satisfy the increase in demand for CPT. Moreover, SAR studies have allowed for the development of more potent CPT analogues topotecan and irinotecan. Unfortunately, resistance has already occurred in several tumour lines. Additional studies are needed to better understand the relationship between substituents and resistance, its clinical relevance and the impact of related gene polymorphism. One of the latest research approaches focuses on modifying the delivery mode to improve tumour cell uptake and reduce toxicity [1].